Negativity in Massive Online Open Courses: Impacts on Learning and Teaching and How Instructional Teams May Be Able to Address It - Denise Comer; Ryan Baker; Yuan Wang (Park University, 2015)
There are many positive aspects of teaching and learning in Massive Online Open Courses (MOOCs), for both instructors and students. However, there is also a considerable amount of negativity in MOOCs, emerging from learners on discussion forums and through peer assessment, from disciplinary colleagues and from public discourse around MOOCs. Through mixed-methods case-study research of two diverse MOOCs (one focused on general, introductory-level content and one designed for specialized graduate students and professionals), we consider the following questions: What are the various forms that negativity takes in MOOCs? How might MOOC negativity vary among disciplines? How does negativity impact MOOC instructors and learners? We present evidence suggesting that MOOC negativity poses a serious problem that may be responsible for instructor/ learner disengagement and instructor burnout, and that anticipating and addressing such negativity can improve MOOC learning communities. Lessons learned from these two MOOCs can be beneficial not only to those involved with MOOCs, but also to those involved in other online educational contexts where faculty and learners seek to manage existing and anticipated negativity.